Особливості забезпечення кібербезпеки - Присяжнюк, М.М.; Цифра, Є.І (Реєстрація, зберігання і обробка даних, 2017)
Проведено аналіз історичних передумов виникнення поняття «кіберпростір», розкрито особливості кіберзагроз, здійснено порівняльний аналіз стратегій кібербезпеки провідних країн світу, наведено комплекс проблем вітчизняної кібербезпекової сфери, обґрунтовано необхідність створення загальнодержавної системи забезпечення кібербезпеки та показано першочергові пріоритети та завдання щодо протидії загрозам у кіберпросторі України. Проведен анализ исторических предпосылок возникновения понятия «киберпространство», раскрыты особенности киберугроз, осуществлен сравнительный анализ стратегий кибербезопасности ведущих стран мира, приведен комплекс проблем отечественной сферы кибербезопасности, обоснована необходимость создания общегосударственной системы обеспечения кибербезопас-ности и приведены первоочередные приоритеты и задания по противодействию угрозам в киберпространстве Украины. Modern onrush of information technologies, informatisation, computerisation and creation of global information space formed fundamentally new substances — information society, information- and cyberspace, which have inexhaustible potential and become instrumental in economic and social development of all countries. Globalization conduces to the rapid information exchange that allows more effective development of humanity. At the same time privileges of modern cyberspace produced row of problems connected to vulnerability of information sphere to cyber threats. Therefore there is a need for a reliable cybernetic security system. The analysis of historical factors of «cyberspace» concept creation is conducted in the article, the features of cyber threats are opened up, the comparative analysis of cyber security strategies of leading countries is carried out, the complex of problems of domestic cyber security is pointed, the necessity of creation of the national cyber security system is substantiated and top priorities and tasks of counteraction threats in the cyberspace of Ukraine are pointed.